Construction operations and excavated materials - Chan, Guo Zhen (2015)
Efficiency is always a topic of interests in any industry and is especially true in the civil industry where frequent delays occur. This is due to the fact that efficiency directly influences costs and will thus affect the profits of a project. There are many sectors of the civil industry and the disposal of excavated materials is one of them. The disposal of excavated materials is done at staging grounds in Singapore and there has been little change to how it is done since the start. However, recently there is a new method of disposing the excavated materials, which is very much different from the past methods. Thus, this report and the research surrounding it aims to find out the different factors affecting the efficiency of staging grounds. The efficiency of the discharge will be measured by using the cycle times defined in the report. Cycle time is calculated by equations factoring the time needed for the discharge of excavated materials that make up the entire cycle. For us to be able to do this, the discharging of materials needs to be broken down to specific parts for data required to be gathered before it is used in the formulas. With the collected data, a model can be used to determine the efficiency of discharging of the excavated materials. Through this research, it is intended that future staging grounds can work on the different details in order to improve the overall efficiency of the disposal of excavated materials.